HEPATITIS C IN THE BRAZILIAN PUBLIC HEALTH CARE SYSTEM: BURDEN OF DISEASE - Castelo, Adauto; Mello, Carlos Eduardo BrandÃo; Teixeira, Rosangela; Madruga, Jose Valdez Ramalho; Reuter, Tania; Pereira, Leila Maria Moreira Beltrão; Silva, Giovanni Faria; Álvares-da-silva, Mario Reis; Zambrini, Heverton; Ferreira, Paulo Roberto Abrão (Instituto Brasileiro de Estudos e Pesquisas de Gastroenterologia e Outras Especialidades - IBEPEGE., 2018)
ABSTRACTBACKGROUND:Infection by hepatitis C virus is one of the leading causes of chronic hepatitis C and cause severe burden for patients, families and the health care system.OBJECTIVE:The aims of this research were to assess the severity of liver fibrosis, comorbidities and complications of hepatitis C virus; to examine health-related quality of life (HRQoL), productivity loss and resource use and costs in a sample of Brazilian chronic hepatitis C, genotype 1, patients.METHODS:This was a cross-sectional multicenter study performed in genotype-1 chronic hepatitis C patients to assess disease burden in the Brazilian public health care system between November 2014 and March 2015. Patients were submitted to a liver transient elastography (FibroScan) to assess liver fibrosis and answered an interview composed by a questionnaire specifically developed for the study and three standardized questionnaires: EQ-5D-3L, HCV-PRO and WPAI:HepC.RESULTS:There were 313 subjects enrolled, with predominance of women (50.8%), caucasian/white (55.9%) and employed individuals (39.9%). Mean age was 56 (SD=10.4) years old. Moreover, 42.8% of patients who underwent FibroScan were cirrhotic; the most frequent comorbidity was cardiovascular disease (62.6%) and the most frequent complication was esophageal varices (54.5%). The results also showed that “pain and discomfort” was the most affected HRQoL dimension (55.0% of patients reported some problems) and that the mean HCV-PRO overall score was 69.1 (SD=24.2). Regarding productivity loss, the most affected WPAI:HepC component was daily activity (23.5%) and among employed patients, presenteeism was more frequent than absenteeism (18.5% vs 6.5%). The direct medical costs in this chronic hepatitis C sample was 12,305.72USD per patient in the 2 years study period; drug treatment costs represented 95.9% of this total.CONCLUSION:This study showed that most patients are cirrhotic, present high prevalence of cardiometabolic diseases and esophageal varices, reduced HRQoL mainly in terms of pain/discomfort, and work productivity impairment, especially presenteeism. Additionally, we demonstrated that hepatitis C virus imposes an economic burden on Brazilian Health Care System and that most of this cost is due to drug treatment.

RESUMOCONTEXTO:A infecção pelo vírus da hepatite C (HCV) é uma das principais causas de hepatite C crônica e provoca implicações graves para pacientes, familiares e sistema de saúde.OBJETIVO:Os objetivos deste estudo foram: analisar a gravidade da fibrose hepática, comorbidades e complicações da hepatite C; examinar a qualidade de vida relacionada à saúde (QVRS), a perda de produtividade e o uso de recursos e custos no sistema público por pacientes brasileiros com hepatite C crônica, genótipo tipo 1.MÉTODOS:Foi realizado um estudo transversal, multicêntrico em pacientes com hepatite C crônica genótipo-1 para avaliar a carga da doença no sistema público de saúde brasileiro entre novembro de 2014 e março de 2015. Os pacientes foram submetidos a uma elastografia hepática transitória (FibroScan) para avaliar a fibrose e a uma entrevista composta por um questionário desenvolvido para o estudo e cinco questionários padronizados: EQ-5D-3L, HCV-PRO, e WPAI:HepC.RESULTADOS:Foram recrutados 313 pacientes. A amostra foi composta predominantemente por mulheres (50,8%), caucasianos/brancos (55,9%) e indivíduos empregados (39,9%). A média de idade foi 56 (DP=10,4) anos. Em média, os pacientes com HCV esperaram 40,6 (DP=49,6) meses entre o diagnóstico e o primeiro tratamento. Ademais, 42,8% dos pacientes que realizaram o FibroScan tinham cirrose; a comorbidade mais frequente foi doença cardiovascular (62,6%) e a complicação mais comum as varizes esofágicas (54,5%). Os resultados também mostraram que “dor e desconforto” foi a dimensão de QVRS mais afetada (55,0% dos pacientes relataram alguns problemas) e que a média do escore do HCV-PRO foi 69,1 (DP=24,2). Em relação à perda de produtividade, o componente do WPAI:HepC mais afetado foi atividade diária (23,5%) e entre os pacientes empregados, presenteísmo foi mais frequente do que absenteísmo (18,5% vs 6,5%). Os custos diretos médicos totais com essa amostra foi de 12.305,72USD por paciente em um período de dois anos; o tratamento medicamentoso representou 95% desse total.CONCLUSÃOEsse estudo mostrou a maioria dos pacientes possui cirrose, apresenta alta prevalência de doenças cardiometabolicas e varizes esofágicas, QVRS reduzida principalmente em termos de dor/desconforto e dano na produtividade, especialmente presenteísmo. Adicionalmente, nós demonstramos que o HCV impõe uma carga econômica no sistema de saúde brasileiro e que os medicamentos correspondem à maioria dos custos.
Hepatite C no sistema público de saúde brasileiro: impacto da doença
Keywords: Hepatitis C; Liver cirrhosis; Quality of life; Cost of illness; Hepatite C; Cirrose hepática; Qualidade de vida; Efeitos psicossociais da doença